Mismatch Negativity and Loudness Dependence of Auditory Evoked Potentials among Patients with Major Depressive Disorder, Bipolar II Disorder, and Bipolar I Disorder - Yang Rae Kim (Brain Sciences, 2020)
Mismatch negativity (MMN) and loudness dependence of auditory evoked potentials (LDAEP), which are event-related potentials, have been investigated as biomarkers. MMN indicates the pre-attentive function, while LDAEP may be an index of central serotonergic activity. This study aimed to test whether MMN and LDAEP are useful biological markers for distinguishing patients with bipolar disorder (BD) and major depressive disorder (MDD), as well as the relationship between MMN and LDAEP. Fifty-five patients with major depressive episodes, aged 20 to 65 years, who had MDD (n = 17), BD type II (BIID) (n = 27), and BD type I (BID) (n = 11), were included based on medical records. Patients with MDD had a higher MMN amplitude than those with BID. In addition, the MMN amplitude in F4 positively correlated with the Korean version of mood disorder questionnaire scores (r = 0.37, p = 0.014), while the MMN amplitude in F3 correlated negatively with LDAEP (r = −0.30, p = 0.024). The odds ratios for the BID group and some variables were compared with those for the MDD group using multinomial logistic regression analysis. As a result, a significant reduction of MMN amplitude was found under BID diagnosis compared to MDD diagnosis (p = 0.015). This study supported the hypothesis that MMN amplitude differed according to MDD, BIID, and BID, and there was a relationship between MMN amplitude and LDAEP. These findings also suggested that BID patients had a reduced automatic and pre-attentive processing associated with serotonergic activity or N-methyl-D-aspartate receptor.